Pengembangan Sistem Informasi Pendaftaran Pesantren berbasis Website (Studi Kasus: Pesantren Mahasiswa FIRDAUS Malang) - Syauqi El Rahman; Denny Sagita Rusdianto; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Pesantren Mahasiswa FIRDAUS is one of the Islamic boarding schools that open registration every year. The registration process is carried out by purchasing a registration form available at the pesantren location. The students who apply are freshmen from out of town. These students have problems buying registration forms because they are still in their hometowns. And the activity of managing registration also experienced problems in managing the quota of new students because the status of being accepted as a student was based on the time of payment. To answer the obstacles mentioned earlier, a solution was given in the form of a registration system that has the function of accepting registration and payment. The process of forming this system begins with the elimination and analysis of needs and generates 20 functional needs and one non-functional need. Then the design process and implementation process are carried out with the Model-View-Controller architectural pattern which is supported by the Codeigniter framework and the implementation of payment functions is supported by Midtrans's payment gateway service. In the next stage, testing was conducted on the implementation of the system. Testing was carried out using white-box testing, using the unit testing method which resulted in 100% valid status, and integration testing which also resulted 100% valid status. Then, black-box testing was carried out using the validation testing method on 33 test cases, which resulted in 100% valid status and also compatibility testing which resulted that the system can work well on 7 types of web browsers.